Low-complexity FDE method for TS-OFDM signal under higher time-varying channels - Reangsuntea, Pongsathorn; Mori, Kazuo; Kobayashi, Hideo; Reangsuntea, Arttapol; Boonsrimuang, Pisit (My University, 2016)
A losing of orthogonality among subcarriers in higher time-varying fading channels causes an inter-carrier interference (ICI) in orthogonal frequency division multiplexing (OFDM) signal which leads a fatal degradation both for the channel estimation accuracy and bit error rate (BER) performances. To solve this problem, this paper firstly proposes a channel estimation method with a new design of time domain training sequence (TS) of using a triangular window function which can achieve higher channel estimation accuracy with keeping lower leakage of power spectrum density (PSD) at the outside of OFDM allocated frequency bandwidth than the conventional TS signal. Secondly, this paper proposes a low-complexity frequency domain equalization (FDE) method which can achieve better BER performance than the conventional one-tap FDE method. The feature of proposed FDE method is to enable the reduction of complexity by using a Maclaurin's expansion algorithm in the inverse matrix calculation. This paper presents various computer simulation results to demonstrate the effectiveness of proposed FDE method as comparing with the conventional FDE methods.
Keywords: frequency domain equalization (FDE); Inter-carrier interference (ICI); PSD; training sequence (TS); TS-OFDM